Hypertension in the South African public healthcare system: a cost-of-illness and burden of disease study. Issue 2 (22nd February 2022) - Kohli-Lynch, Ciaran N; Erzse, Agnes; Rayner, B; Hofman, Karen J
Abstract : Objectives: To quantify the health and economic burden of hypertension in the South African public healthcare system. Setting: All inpatient, outpatient and rehabilitative care received in the national public healthcare system. Participants: Adults, aged ≥20 years, who receive care in the public healthcare system. Outcomes: Worksheet-based models synthesised data from multiple sources to estimate the burden of disease, direct healthcare costs, and societal costs associated with hypertension. Results were disaggregated by sex. Results: Approximately 8.22 million (30.8%, 95% CI 29.5% to 32.1%) South African adults with no private health insurance have hypertension. Hypertension was estimated to cause 14 000 (95% CI 11 100 to 17 200) ischaemic heart disease events, 13 300 (95% CI 10 600 to 16 300) strokes and 6100 (95% CI 4970 to 7460) cases of chronic kidney disease annually. Rates of hypertension, hypertension-related stroke and hypertension-related chronic kidney disease were greater for women compared with men. The direct healthcare costs associated with hypertension were estimated to be ZAR 10.1 billion (95% CI 8.98 to 11.3 billion) or US0.711 billion (95% CI 0.633 to 0.793 billion). Societal costs were estimated to be ZAR 29.4 billion (95% CI 26.0 to 33.2 billion) or US2.08 billion (95% CI 1.83 to 2.34 billion). Direct healthcare costs were greater for women (ZAR 6.11 billion or US0.431 billion) compared with men (ZAR 3.97 billion or US0.280 billion). Conversely, societal costs were lower for women (ZAR 10.5 billion or US0.743 billion) compared with men (ZAR 18.9 billion or US1.33 billion). Conclusion: Hypertension exerts a heavy health and economic burden on South Africa. Establishing cost-effective best practice guidelines for hypertension treatment requires further research. Such research will be essential if South Africa is to make progress in its efforts to implement universal healthcare.